The Influence of Emotional Regulation on Public Speaking Skills of Students of the Informatics Education and Computer Engineering Study Program, Makassar State University - Lisah Febrianti; Sugeng A. Karim; Dwi Rezky Anandari Sulaiman (PT. Global Research Collaboration, 2026)
Public speaking ability is an essential skill for students to support academic and professional success and is influenced by emotion regulation. Emotion regulation helps individuals control anxiety, enhance self-confidence, and maintain emotional stability when speaking in public. This study aimed to determine the level of public speaking ability, the level of emotion regulation, and the effect of emotion regulation on public speaking ability among students of the 2020 cohort in the Informatics and Computer Engineering Education Study Program at Universitas Negeri Makassar. A quantitative ex post facto research design was used, with data collected through questionnaires from 132 students selected based on the Krejcie and Morgan table. Emotion regulation was treated as the independent variable, while public speaking ability was the dependent variable, and data were analyzed using descriptive statistics and simple linear regression. The results showed that 77.27% of students had high public speaking ability and 62.87% had high emotion regulation, with regression analysis indicating a significance value of 0.00 (<0.05) and a coefficient of determination of 71%, demonstrating a significant effect of emotion regulation on public speaking ability and indicating that better emotional management is associated with better public speaking performance, although other factors also contribute.